Why Some Countries Can Escape the Fiscal Pro-Cyclicality Trap and Others Cannot ? - Herrera, Santiago; Kouame, Wilfred A.; Mandon, Pierre (World Bank, Washington, DC, 2019)
This paper analyzes the procyclicality of fiscal policy on the tax and spending sides in a sample of 116 developing countries between 2000 and 2016. About 20 percent of the countries in the sample switched from procyclical to countercyclical policy stance. In Sub-Saharan Africa, 30 of 39 countries remained caught in the procyclicality trap and the region has the highest degree of procyclicality. The Middle East and North Africa region switched from a countercyclical policy stance to a procyclical one over time. The Europe and Central Asia and Latin America and the Caribbean regions significantly reduced the degree of procyclicality. The main economic variables that affect procyclicality are financial depth, tax base variability, and natural resource dependence. In line with the political economy literature, the perception of corruption, social fragmentation, and inequality in resource distribution are positively associated with procyclicality. The findings also show that the quality of fiscal institutions is associated with procyclicality; countries with fiscal rules have smaller procyclical bias, but the effect is not homogeneous; and higher degrees of expenditure rigidity are associated with lower procyclical bias. The study finds asymmetric policy stances along the business cycle, with procyclicality being more pronounced during recessions. Similarly, the political cycle affects procyclicality, as procyclical bias increases in electoral years. From the tax management perspective, procyclical bias is still present, but there are significant changes: most of the political economy variables lose significance; the resource-dependence variable is not significant; external credit availability reduces procyclicality; tax base variability increases procyclical bias; and expenditure rigidity is no longer significant, but fiscal space becomes determinant of procyclical bias.